2009
DOI: 10.1080/00016340903176818
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin stimulates myometrial contractility and cervical remodeling in vitro

Abstract: A possible underlying mechanism for the shortened labor time after low molecular weight heparin treatment is enhanced myometrial contractility and an increased IL-8 secretion in cervical fibroblast, mimicking the final cervical ripening in vivo. Our data support the notion that anticoagulant activity is not required to promote labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…Our findings may imply a role of LMWH on duration and initiation of labour Similar as those reported by Ekman and coworkers [10]. They also report in a laboratory setting that LMWH stimulates myometrial contractility and cervical remodeling in vitro [14]. This theory would also give an explanation to the increased risk of prematurity.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings may imply a role of LMWH on duration and initiation of labour Similar as those reported by Ekman and coworkers [10]. They also report in a laboratory setting that LMWH stimulates myometrial contractility and cervical remodeling in vitro [14]. This theory would also give an explanation to the increased risk of prematurity.…”
Section: Discussionsupporting
confidence: 90%
“…The mechanisms of the activator effect of heparin on the LN capsular SM cells are not quite clear. The stimulatory effect of heparin on SM contractility was previously observed on other objects [6] and could be due to changes in the physicochemical characteristics of the perimembrane layer. Modifi cation of interactions between glycoproteins of the plasma and lymph and calcium channels in the plasmalemma under the effect of heparin has been demonstrated [9].…”
Section: Resultssupporting
confidence: 55%
“…Ekman-Ordeberg and colleagues. [67] have demonstrated that low molecular weight heparin increased IL-8 secretion in cervical fibroblasts. This area of research has great potential for targeting the mechanisms involved in cervical change during pregnancy.…”
Section: Importance Of the Studymentioning
confidence: 96%